Expression and distribution of the complement receptor gC1qR in bovine sperm - Valeris, Robert; Villamediana, Patricia; Quintero, Armando; Parra, Omaira; Sandoval, Jorge; Ghebrehiwet, Berhane (Revista Científica de la Facultad de Ciencias Veterinarias)
The complement receptor gC1qR/p33, which recognizes the globular heads of C1q, is a multicompartmental and multifunctional protein and has been shown to play a role in reproduction in humans. The objective of this research was to determine the gC1qR distribution and expression on plasma membrane in bovine sperm before and after heparin treatment. Thus, capacitation of sperm derived from frozen-thawed bovine semen was induced through heparin incubation and its effectiveness was assessed with a CTC stain. Subsequently, indirect immunofluorescence assays were conducted with mAb (60.11, anti-gC1qR) to assess gC1qR distribution and expression. Data analysis demonstrated that gC1qR is expressed on the plasma membrane of bovine sperm. gC1qR showed a capacitation-related redistribution, migrating to the acrosome region: 175 sperm in heparin-incubated aliquots vs. 109 in control (P<0.05, n=300) showed fluorescence over the acrosome region. This distribution is similar to that reported in humans. Similarly, either gC1qR expression or its accessibility to antibodies increased after capacitation. This also correlates with what has been observed in humans. These results suggest that gC1qR could participate in primary sperm-oocyte interaction in bovines.